The place and the role of renewable energy sources in energy policy of the European Union - Baikushikova, G. (International relations and international law Journal, 2016)
The article is focuses on the scientific analysis of the renewable energy, organization and prospects of its using by the example of the European Union. There is also an attempt to identify the place and role of alternative energy sources in the EU energy policy today, prospects and limits the development of such alternative energy. The author studies the causes of active using of alternative energy sources in the European Union. In the «New EU energy policy», approved in 2008, was included strategic objective «best use of its own energy resources of the EU» through energy efficiency and development, along with the traditional (non-renewable and dwindling), alternative renewable energy sources (RES) by increasing their share in the energy balance up to 20% by 2020. The article also analyzes the main types of renewable energy sources (wind, solar, biomass, mini-hydroelectric station), the achieved progress in this area and forecasts of its development.